2011
DOI: 10.1371/journal.pone.0025515
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Stem Cell Marker Prominin-1/CD133 in the Uptake of Transferrin and in Iron Metabolism in Human Colon Cancer Caco-2 Cells

Abstract: As the pentaspan stem cell marker CD133 was shown to bind cholesterol and to localize in plasma membrane protrusions, we investigated a possible function for CD133 in endocytosis. Using the CD133 siRNA knockdown strategy and non-differentiated human colon cancer Caco-2 cells that constitutively over-expressed CD133, we provide for the first time direct evidence for a role of CD133 in the intracellular accumulation of fluorescently labeled extracellular compounds. Assessed using AC133 monoclonal antibody, CD133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 88 publications
3
53
0
Order By: Relevance
“…In addition, the intracellular ICC signal of the CD133/1 mAb, both in 2D and 3D was similar to the granular pattern of Dylight 549 labeled anti-CD133/1 mAb obtained by confocal microscopy. This indicates that in addition to plasma membrane expression, a substantial amount of the CD133-receptor is also expressed in the cytoplasm which is consistent with other reports [33,34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the intracellular ICC signal of the CD133/1 mAb, both in 2D and 3D was similar to the granular pattern of Dylight 549 labeled anti-CD133/1 mAb obtained by confocal microscopy. This indicates that in addition to plasma membrane expression, a substantial amount of the CD133-receptor is also expressed in the cytoplasm which is consistent with other reports [33,34].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the BxPC3 cells displayed reduced viability (~50 %) when exposed to the CD133/1 (AC133) mAb only, suggesting that blocking the CD133 receptor may affect the cell viability or growth in this cell line. The mechanism behind this is currently unclear; however, it was recently shown that the blockage of the CD133 receptor of un-differentiated human colorectal Caco-2 cells by using the AC133 antibody resulted in a significant reduction of the uptake of transferrin [33]. In addition, since transferrin is an essential factor for the proliferation of pancreatic cancer cells [35], this may explain the cytotoxic effects of AC133 in the BxPc3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…external factors such as the environment or habits that lead individuals exposed to substances that are carcinogenic, systemic disease, drugs, etc. 4 Whereas internal factors are including the factors, which are found in the body such as the genetic, hereditary carried by each individual, the cancer stem cell (CSC) and growth factors that exist in the surrounding environment such as cells and other hormone. 5 CSC defines as a small subpopulation of cancer cells that form a pool of autonomous cell with the exclusive ability to make the heterogeneous lineages of cancer cells that comprehend the tumor.…”
Section: Research Report Introductionmentioning
confidence: 99%
“…These lesions including: mucocel, papilloma, fibroepitelial polyp and epulis. 4,25 materials and methods A cross sectional observational research was carried out on patients who have suffered premalignant lesion (PML: leukoplakia, erythroplakia, oral lichen planus, lichenoid reaction, and submucous fibrosis.) and proliferative lesion (PL) such as papilloma, fibroma, epulis, and cysts that seek treatment to oral medicine clinic under informed consent.…”
mentioning
confidence: 99%
“…CD133 is a pentaspan trans-membrane protein that is detected by an antibody binding to its two glycosylated extracellular moieties [9,10]. Whilst its function is not clearly understood, this glycoprotein is localised to cell membrane protrusions and microvilli, where it associates with cholesterol domains, suggesting a functional role in membrane transport processes [11,12].…”
Section: Introductionmentioning
confidence: 99%